Conceptualizing humans as animals in English verb particle constructions - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Klaus-Uwe Panther Nanjing Normal University, China, and University of Hamburg, Germany Linda L. Thornburg Nanjing Normal University, China   ABSTRACT Verb particle constructions with animal names used as verbs ('VPrt critter constructions'), such as horse around, clam up, and rat out, are interesting because of their (i) grammatical structure, (ii) pragmatic function, (iii) conceptual content, and (iv) the cultural knowledge they reflect. This chapter focuses on the latter two aspects of critter constructions. More specifically, we assume that an adequate analysis of critter constructions requires folk or cultural models of the animals in question, spatial schemas for the particle, metaphorical mappings and metonymic inferences, and aspectual categories in the sense of Vendler (1957). We place our findings in the larger context of the status of cultural and cognitive models in general. Such models (including animal folk models) are often outdated and reflect centuries-old beliefs that have left their traces in lexico-grammatical structure, in this case, critter constructions.